Labor dystocia due to lower uterine segment myoma: A case study and literature review (Indian Journal of Case Reports, 2025)
Pregnancy-related complications include miscarriage, preterm birth, preterm placental abruption, postpartum hemorrhage, and a high rate of cesarean section. We hereby present a case of undiagnosed lower uterine segment fibroid located posteriorly causing obstructed labor and stillbirth, reported in a teaching hospital, Autonomous State Medical College, Fatehpur, catering to rural areas. Lack of adequate antenatal care is still a major shortcoming of the Indian Health system. Varied case reports show a tailored approach for fibroids in pregnancy.